'At Home on the Earth'. (5th March 2021) - Dean, Dorothy C.
Abstract : The climate crisis requires a revaluation of what it means to be human that radically rejects human exceptionalism. I argue that such an account of human being can be constructed from a combination of Sallie McFague's theology and Maurice Merleau-Ponty's phenomenology. While McFague's theology established the parameters for an embodied, ecotheological concept of human being, I contend that Merleau-Ponty's late work can push this vision of humanity from being anti-anthropocentric to being truly non-exceptionalistic, by making it possible to understand humans as part of the 'mesh' of the world. This allows for a human non-exceptionalism that still has room for the differentiation and relationality necessary to honor human diversity and to facilitate ameliorative action. The result is a foundation for a new ecotheological concept of human being that can speak to what it means to be human in the Anthropocene.